2011
DOI: 10.1158/1541-7786.mcr-10-0526
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid-Modified Estrogen Derivative that Treats Breast Cancer Independent of Estrogen Receptor Expression through Simultaneous Induction of Autophagy and Apoptosis

Abstract: It is a challenge to develop a universal single drug that can treat breast cancer at single or multiple-stage complications, yet remains nontoxic to normal cells. The challenge is even greater when breast cancer-specific estrogen-based drugs are being developed which cannot act against multi-staged breast cancer complications owing to cells’ differential ER expression status and their possession of drug-resistant and metastatic phenotypes. We report here the development of a first cationic lipid-conjugated est… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 36 publications
1
75
0
Order By: Relevance
“…Inclusion of ES to other cationic lipids (C8, C12) induces selectivity but offers limited anticancer effect in broad range of cancer cells. We believe, 5c targeted and modulated the ER and/or its existing pathways unfavorably and selectively in ER ± breast cancer cells (and also in ER þ non-breast cancer cells), as like ES-C8 (here, 5b) did in ER ± breast cancer cells through induction of apoptosis and autophagy [18].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Inclusion of ES to other cationic lipids (C8, C12) induces selectivity but offers limited anticancer effect in broad range of cancer cells. We believe, 5c targeted and modulated the ER and/or its existing pathways unfavorably and selectively in ER ± breast cancer cells (and also in ER þ non-breast cancer cells), as like ES-C8 (here, 5b) did in ER ± breast cancer cells through induction of apoptosis and autophagy [18].…”
Section: Discussionmentioning
confidence: 83%
“…Previously we found that ES-C8 was the most potent anticancer molecule known among this class of molecules [18]. Here, ES-C10 (5c) exhibited 5e12 folds lesser IC 50 than IC 50 exhibited by ES-C8 (5b) in different cancer cells.…”
Section: Antiproliferative Activitymentioning
confidence: 73%
See 3 more Smart Citations